Optimization Employee Performance Through Role Work Life Balance And Work Environment - Fikri, Muchammad; Wahyu Utomo, Kabul; Hidayah, Zainur (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the influence of work-life balance and work environment on employee performance, with job satisfaction and organizational commitment as intervening variables. Data collection in this study was conducted through a survey approach with a descriptive quantitative research type, by distributing questionnaires to 103 respondents. The data analysis tool used in this study is SmartPLS 4.0. The results of this study indicate that, partially, work-life balance and job satisfaction have a positive and significant effect on performance. Partially, the work environment and organizational commitment have a positive but not significant effect on performance. Partially, work-life balance and work environment have a positive and significant effect on job satisfaction. Work-life balance has a positive but not significant effect on organizational commitment. The work environment has a positive and significant effect on organizational commitment. Job satisfaction mediates the effect of work-life balance on performance and the effect of the work environment on performance. Organizational commitment does not mediate the effect of work-life balance on performance nor the effect of the work environment on performance. Keyword: Work Life Balance, Work Environment, Job Satisfaction, Organizational Commitment, Employee Performance